2013
DOI: 10.2903/j.efsa.2013.3422
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety of “coriander seed oil” as a Novel Food ingredient

Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver a scientific opinion on "coriander seed oil (CSO)" as a novel food ingredient (NFI) in the context of Regulation (EC) No 258/97. Petroselinic acid (PA) is the major fatty acid in CSO. Conventional edible oil technologies are used to manufacture the NFI. The NFI is intended to be marketed as a food supplement for healthy adults, at a maximum level of 600 mg per day (i.e. 8.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
2
Order By: Relevance
“…Freires et al [34] demonstrated through pharmacogenomic analysis that the CLEO and its selected active fraction had low cytotoxicity on human cells. The CSEO (16 mg/plate) was tested negative for mutagenicity in the absence and presence of metabolic activation among the S. typhimurium strains tested [9]. In the evaluation of plant extract toxicity by the brine shrimp bioassay, the partial lethal concentration (LC 50 ) value of <1000 mg/mL has been considered bioactive [46] ; Soares et al [35] demonstrated that the C. sativum fruit EO had LC 50 value of 23 mg/mL.…”
Section: Safety and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Freires et al [34] demonstrated through pharmacogenomic analysis that the CLEO and its selected active fraction had low cytotoxicity on human cells. The CSEO (16 mg/plate) was tested negative for mutagenicity in the absence and presence of metabolic activation among the S. typhimurium strains tested [9]. In the evaluation of plant extract toxicity by the brine shrimp bioassay, the partial lethal concentration (LC 50 ) value of <1000 mg/mL has been considered bioactive [46] ; Soares et al [35] demonstrated that the C. sativum fruit EO had LC 50 value of 23 mg/mL.…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…The CSEO is intended to be marketed as a food supplement for healthy adults, at a maximum level of 600 mg per day [9] . The seeds are rich source of lipids, 28.4% of the total seed weight, which may be of great importance in the food industry [6].…”
Section: Usage and Nutritional Valuementioning
confidence: 99%
“…Subsequently, in 2014, the marketing of chia oil was authorized [16]. Other example includes coriander seed oil (Coriandrum sativum), with a richness in monounsaturated fatty acids (MUFA) of 68-90% that is attributable mainly to its content of petroselinic acid (60-75%) (18:1 n-6) [17].…”
Section: Introductionmentioning
confidence: 99%
“…ЖКО, як побі-чний продукт виробництва ефірної коріандрової олії, застосовується у промислових виробництвах при виго-товленні мастильних матеріалів [7]. У роботі [8] було науково обґрунтовано безпечне вживання ЖКО в яко-сті нового харчового інгредієнту в раціоні людини. Однак нерафінована ЖКО має специфічний аромат та смак.…”
Section: огляд літературиunclassified